Strengthening MSME Performance: The Role of Entrepreneurial Orientation and Business Models in Micro Wakaf Bank PKP - Nurinda, Shaqyna Ratu; Effendi , Syahrul; Ardheta, Preztika Ayu (SAN Scientific, 2025)
This research aims to determine to analyze the effect of entrepreneurial orientation on the performance of MSMEs on customers of the Pondok Karya Pembangunan Micro Waqf Bank (PKP) and to analyze the effect of the Business Model on the performance of MSMEs on customers of the Micro Waqaf Bank Pondok Karya Pembangunan (PKP) Development Work. The population of this study was 100 customers of the PKP Micro Waqf Bank. Sample selection through non-probability sampling method with purposive sampling technique. The results of this study indicate that Entrepreneurial Orientation and Business Model have a positive and significant influence on MSME Performance on customers of the Pondok Karya Pembangunan Micro Waqf Bank (PKP). The managerial implications of this study emphasize the need for Micro Wakaf Bank Pondok Karya Pembangunan (PKP) to enhance entrepreneurial orientation and optimize business models among its UMKM customers. By fostering innovation, proactive risk-taking, and competitive aggressiveness, the bank can empower UMKM to adapt to market dynamics effectively. Simultaneously, developing flexible and customer-centric business models can improve operational efficiency and market responsiveness. These strategies not only drive better performance outcomes for UMKM but also strengthen the bank's role as a facilitator of sustainable economic growth in the community.